The Raging Storm: Warriors: a Vision of Shadows #6 - Hunter, Erin (New York, NY : Harper, an imprint of HarperCollins Publishers, 2019)
"As StarClan warns of an oncoming storm, the five warrior Clans by the lake must decide what they are willing to sacrifice to make a permanent home among them for SkyClan"--Provided by publisher.
new kids book 2023 spring.
4.3.
5-8
600
Accelerated Reader AR
Keywords: Adventure and adventurers -- Fiction; Fantasy; Wilderness survival; Fantasy fiction; Feral cats; Clans; Juvenile fiction; Prophecies; Cats -- Fiction; Social conflict -- Fiction